Autonomía jurisdiccional indígena : fuero especial y archipiélago penitenciario (2017)
"The Colombian legal system has not yet produced a normative instrument that can legally define the coordination system between the ordinary jurisdiction and the indigenous special jurisdiction. Among the most sensitive phenomena of the inevitable inter-jurisdictional interaction, the imprisonment of indigenous in ordinary prisons stands out as one of the most significant points of contact, both, due to its potential to impact its own legal systems, and because of the contradictions that it entails and which confront it with multiculturalism as a constitutional principle. The text that is given here presents the rules that make up the coordination system with regard to the imprisonment and/or execution of prison sentences for indigenous persons in Colombia, in the terms in which the constitutional jurisprudence has arranged in order to discipline the interrelation between the two orders." -- Tomado del Formato de Documento de Grado.